2019
DOI: 10.3390/ijms20215256
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Genetic Engineering for Disease Resistance: Past, Present and Future

Abstract: Worldwide, citrus is one of the most important fruit crops and is grown in more than 130 countries, predominantly in tropical and subtropical areas. The healthy progress of the citrus industry has been seriously affected by biotic and abiotic stresses. Several diseases, such as canker and huanglongbing, etc., rigorously affect citrus plant growth, fruit quality, and yield. Genetic engineering technologies, such as genetic transformation and genome editing, represent successful and attractive approaches for dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 185 publications
(215 reference statements)
0
37
0
Order By: Relevance
“…Meanwhile, CRISPR is a powerful weapon to combat viruses [52]. However, CRISPR is only a promising tool when the virulence mechanism of CaLas is still vague [45,53]. Based on our results and previous reports, we propose that E3 enzymes differential expressed in HLB tolerant and HLB susceptible citrus upon CaLas infection [25] may be considered as the target of CRISPR based on the possibility of CaLas interference with citrus development and disease resistance via targeting the specific proteins of the ubiquitin-proteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, CRISPR is a powerful weapon to combat viruses [52]. However, CRISPR is only a promising tool when the virulence mechanism of CaLas is still vague [45,53]. Based on our results and previous reports, we propose that E3 enzymes differential expressed in HLB tolerant and HLB susceptible citrus upon CaLas infection [25] may be considered as the target of CRISPR based on the possibility of CaLas interference with citrus development and disease resistance via targeting the specific proteins of the ubiquitin-proteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, genome editing ensured by clustered regularly interspaced short palindromic repeats (CRISPR)-based systems is considered as a crucial genetic manipulation tool that can be applied to numerous crops, including citrus. It is in fact established that CRISPR systems, such as CRISPR/CRISPR-associated protein (Cas)9 and CRISPR/Cpf1 systems, can provide a promising new corridor for producing citrus cultivars expressing resistant to different pathogens [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported using CRISPR/Cas9 system [76][77][78][79][80][81] or CRISPR/Cas12 system [82] as an efficient tool for genome editing in citrus. Great efforts have been focused on the improvement of citrus resistance to bacterial canker and HuangLongbing (HLB) through CRISPR/Cas system and conventional transformation strategies [83]. Interestingly, the isolation of monoembryonic early-flowering "Mini-Citrus", its sequence homology to cultivated citrus species, and its amenability to CRISPR/Cas9 precise editing render it a potent model system to study gene functions in citrus [81].…”
Section: Citrus Genetic Modification Approachmentioning
confidence: 99%